Patriarchal Culture, Sexual Violence, and Legal Protection for Women in Indonesia - Nurnaningsih Nurnaningsih (Veteran Law Review, 2023)
Patriarchal culture cannot be separated from women's lives. Male domination over women has become a daily reality in many countries. Patriarchal culture assumes that women are "objects" and men are humans. In this case, men become subjects, and women as objects are regulated by men in various lines of life and culture. The impact of patriarchal culture is to place women who experience sexual violence in a worse position. At the level of the construction of a large Indonesian society that still uses a patriarchal paradigm, women are placed as second-class citizens. As a result, often the statements and reports from women are not heard. A further implication for women victims of sexual violence is that they are re-victimized by society, considered as the party that caused the violence. This article will raise two legal issues related to legal theory and law. The first legal issue in this paper is related to feminist legal theory based on the feminist view that in history, law is to perpetuate the position of women under the subordination of men. After discussing feminist legal theory, the author will discuss the second issue, namely law related to law enforcement in the field of sexual violence and its relation to feminist legal theory. Feminist legal theory is needed in building the basis of statutory norms (legal dogmatics) and the justice system to eliminate all forms of violence, especially sexual violence.